Empirical Analysis of the Interplay between Municipal Waste Generation, Living Standards, and Innovation in the European Union - Cristea, Mirela; Dracea , Raluca Mihaela; Sirghi, Nicoleta; Panzaru, Ciprian; Brancu, Laura (Transformations In Business & Economics, 2025)
The paper examines global interlinkages among the level of municipal waste generation and the representative socio-economic, technological, and innovation factors at the level of the European Union countries. Further, we realize a hierarchical clustering of the European Union member states according to similar characteristics regarding the level of municipal waste generation, jointly with these representative socio-economic and technological factors, in order to propose adequate solutions for lower-performing states. The data covers the 2006-2021 lapse of time, and the research methodology is based on two advanced methods, namely network analysis performed through Gaussian graphical models and cluster analysis performed by the Ward method. The results highlight that the analysis only of municipal waste generation level, without other socio-economic benchmarks, would not be conclusive, as there are developed states with high levels of municipal waste generation, as well as developing countries with waste generation above the EU.
Keywords: municipal waste generation; living standards; innovation; econometric analysis; European Union